2016
DOI: 10.18001/trs.2.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Source Credibility in Tobacco Control Messaging

Abstract: Objectives Perceived credibility of a message’s source can affect persuasion. This paper reviews how beliefs about the source of tobacco control messages may encourage attitude and behavior change. Methods We conducted a series of searches of the peer-reviewed literature using terms from communication and public health fields. We reviewed research on source credibility, its underlying concepts, and its relation to the persuasiveness of tobacco control messages. Results We recommend an agenda for future res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 42 publications
(64 reference statements)
3
81
1
Order By: Relevance
“…Because the primary outcome measure referenced the CDC, differential knowledge of what the CDC is or the extent to which they view the CDC as a credible source may have influenced participants’ responses (Schmidt, Ranney, Pepper, & Goldstein, 2016). The primary outcome measure also used a four-point response scale, which could have limited variability in the participants’ responses.…”
Section: Discussionmentioning
confidence: 99%
“…Because the primary outcome measure referenced the CDC, differential knowledge of what the CDC is or the extent to which they view the CDC as a credible source may have influenced participants’ responses (Schmidt, Ranney, Pepper, & Goldstein, 2016). The primary outcome measure also used a four-point response scale, which could have limited variability in the participants’ responses.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the impact of source credibility (i.e., the perceived credibility or competence of the organization delivering the message) in tobacco communication campaigns (26). Previous research suggests that messages with a credible source are more likely to be positively received and reported as believable than messages without a credible source (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…7 Because the FDA traditionally regulated food and drugs, existing measures of FDA credibility may be inappropriate for understanding public perceptions of FDA credibility around tobacco issues. 8 A study found that in 2009, less than half of US adults were aware of FDA’s authority to regulate tobacco, though many adults were generally supportive of messages about the health risks of tobacco and protective regulations. 9 With tobacco product regulation being vastly different from approving food products and medication, it is necessary to evaluate public perceptions of the FDA’s credibility as a tobacco regulator.…”
mentioning
confidence: 99%
“…8 In an organizational context, expertise reflects the extent to which an organization knows correct information, and trustworthiness is the extent to which an organization is believed to present what it considers correct information. 1 Several studies have identified other dimensions of credibility, such as familiarity with an organization, congruence of its values with one’s personal values, 8,10,11 and social concern. 12 For a government agency or non-profit organization, public interest is likely to be a particularly important component of credibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation